2020
DOI: 10.17503/agrivita.v0i0.2514
|View full text |Cite
|
Sign up to set email alerts
|

Mycoparasitic Activity of Indigenous Trichoderma virens Strains Against Mungbean Soil Borne Pathogen Rhizoctonia solani: Hyperparasite and Hydrolytic Enzyme Production

Abstract: Rhizoctonia solani is one of the harmful pathogens on mungbean, which is very challenging to be controlled. T. virens has been studied intensively and has great potency to control R. solani through mycoparasitism. Seven strains of T. virens isolated from various rhizospheres were tested for their mycoparasitic potential by observing their hyperparasitism and the production of hydrolytic enzymes. All strains showed the ability to suppress the growth of R. solani on dual culture assay as well as on culture filtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…This has been demonstrated for R. solani, not only in dual culture tests [63][64][65] but also in field experiments, including crops like sugar beet [63], potato [66], cucumber [67], bean [68], tobacco [69], maize [70], cowpea [33] and tomato [33]. It has been well documented that Trichoderma suppresses R. solani through mycoparasitism and the production of antifungal compounds [66,71,72]. Moreover, various Trichoderma species have shown great potential in suppressing tomato wilt caused by F. oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 95%
“…This has been demonstrated for R. solani, not only in dual culture tests [63][64][65] but also in field experiments, including crops like sugar beet [63], potato [66], cucumber [67], bean [68], tobacco [69], maize [70], cowpea [33] and tomato [33]. It has been well documented that Trichoderma suppresses R. solani through mycoparasitism and the production of antifungal compounds [66,71,72]. Moreover, various Trichoderma species have shown great potential in suppressing tomato wilt caused by F. oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 95%
“…When confronted with each other, C. rosea mycelia extended towards those of B. cinerea and produced many papilla-like outgrowths at the tips of the hyphae, where were active developing regions and sensitive to various stimuli. This kind of infection mechanism was also observed in T. atroviride when parasitizing R. solani and P. ultimum [ 4 ], and the exudates of R. solani could induce the formation of papilla in T. virens [ 43 ].…”
Section: Discussionmentioning
confidence: 85%
“…T. yunnanense, according to [22] also has a solid potential to suppress pathogens such as Phytophthora capsici and C. gloeosporioides. Dual culture testing conducted on two soil-borne fungi, Sclerotinia sclerotiorum and Sclerotium cepivorum, showed that T yunnanense could significantly suppress the growth of these pathogens [25]. 600 bp 500 bp 1kb…”
Section: Molecular Character Of Isolate Trichoderma Spmentioning
confidence: 99%